Hubungan antara pendekatan pengajaran pensyarah terhadap pendekatan pembelajaran serta kesan efikasi kendiri sebagai faktor moderator dalam kalangan pelajar pascasiswazah di Universiti Teknologi Malaysia - Mohd. Ahyan, Nurabidah (2014)
This study aims to identify the relationship between teaching approaches towards learning approaches and the impact of self-efficacy as a mediator among the postgraduate students’ in Universiti Teknologi Malaysia (UTM). Based on the literature reviews, three factors of learning approaches were identified, namely deep approach, surface-rationale and surface-disorganized. While the two factors of teaching approaches which are student-centered and teacher-centered. Self-efficacy has been used as mediating variable. A total of 331 respondents of postgraduate students’ and 175 of lectures from Universiti Teknologi Malaysia (UTM), Skudai gave feedback for this study. Data was collected using questionnaires, and then analyzed using descriptive, univariate and multivariate statistics to answer the research objectives and the relationship between the variables. The findings make it clear that students-centered approach had used most among lecturers. Meanwhile, the deep approach was used among postgraduate students’ in UTM. Moreover, the results also showed that there was a moderate relationship between all the factors of learning approaches and teaching approaches. Further, demonstrated hierarchical regression model also showed that the self-efficacy had impacted the relationship between the teacher approaches and the learning approaches by 17.6%. Several suggestions also were offered to future researchers to improve this research in the future.